Divide and conquer : a comparative history of medical specialization - Weisz, George (Oxford University Press, 2006)
This wide-ranging book is the first to examine one of the most significant and characteristic features of modern medicine - specialization - in historical and comparative context. Based on research in three languages, it traces the origins of modern medical specialization to 1830s Paris and examines its spread to Germany, Britain, and the US, showing how it evolved from an outgrowth of academic teaching and research in the 19th century into the dominant mode of medical practice by the middle of the 20th. Taking account of the parallels and differences in national developments, the book shows the international links among the nations' medical systems as well as the independent influences of local political and social conditions in the move toward specialization. An epilogue takes the story up to the twenty-first century, where problems of specialization merge into the larger crisis of health care which affects most western nations today.